KEBIJAKAN HUKUM PIDANA DALAM MEREHABILITASI NARAPIDANA ANAK - A.Latief Hasjim; Erniwati Erniwati (Justici, 2020)
ABSTRACT Crime or crime does not limit gender and is not monopolized by adults or parents, in fact not even a small number of children are perpetrators of crime, which is generally "blue collar crime" or "blue collar crime". But whatever type of crime is committed, if the crime is serious and dangerous enough, then of course it can be imposed with imprisonment, whose excess is certainly not very good for a child. is the next generation of the nation. The criminal law policy in the field of fostering child convicts within the framework of rehabilitation efforts, is quite complete, governing successively regarding: Legal Policies Regarding Criminal Children and Child Prisoners, Legal Policies Regarding Institutions for Criminal Rehabilitation of Children, Forms and Stages of Child Prisoners Development